2014
DOI: 10.1111/vop.12231
|View full text |Cite
|
Sign up to set email alerts
|

Fluid dynamics and intraocular pressure using venturi phacoemulsification machine in dogs ex vivo

Abstract: BH during the I/A stage could be reduced to avoid unnecessary stress on the canine eye when using a venturi system. Although phacoemulsification with a 3.2-mm CCI could induce lower IOP, a 3.0-mm CCI might lessen the irrigation flow stress on the eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…A previous human study suggested that a reduction in the incisional outflow induced by vitreous plugging of the CCI might increase the static pressures after a PLCR . The IOP fluctuation during phacoemulsification was reported to be determined by the balance between the influx affected by the irrigating fluid and the efflux affected by the aspirating fluid and the leakage through the CCI . Therefore, in addition, the vitreous plugging of the phaco needle or IA tip might act as a flow restrictor, thereby decreasing the efflux of the aspirating fluid and lens materials and hence increasing the IOP during the surgery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A previous human study suggested that a reduction in the incisional outflow induced by vitreous plugging of the CCI might increase the static pressures after a PLCR . The IOP fluctuation during phacoemulsification was reported to be determined by the balance between the influx affected by the irrigating fluid and the efflux affected by the aspirating fluid and the leakage through the CCI . Therefore, in addition, the vitreous plugging of the phaco needle or IA tip might act as a flow restrictor, thereby decreasing the efflux of the aspirating fluid and lens materials and hence increasing the IOP during the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Phacoemulsification was subdivided into two stages: the sculpt‐segment removal (SS) stage, which involved the use of a phacoemulsification handpiece with a 19 G, straight 30° needle (Storz® DP8130, Bausch and Lomb, Rochester, NY, USA), and a soft silicone sleeve, and the irrigation/aspiration (IA) stage, which involved an IA handpiece with a 20 G, 0.3‐mm aspiration port tip (Storz® DP9745, Bausch and Lomb), and a soft silicone sleeve. On the basis of our previous studies, the BHs/vacuum pressures were set at 60 cm/100 mmHg, respectively, as a low fluidic setting for three eyes and at 90 cm/170 mmHg, respectively, as a high fluidic setting for the other three eyes during the SS stage. The IA stage was performed with BHs/vacuum pressures of 60 cm/450 mmHg and 90 cm/450 mmHg for the low and high fluidic settings, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ex vivo models have been used to study a variety of different ocular diseases in different species . One important benefit of an ex vivo model is that it allows for a more adequate representation of in vivo conditions.…”
Section: Introductionmentioning
confidence: 99%